Peran Penjualan dalam Memoderasi Pengaruh Biaya Produksi terhadap Laba - Isna Ardila; Rezki Zurriah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the effect of production costs on profit and to analyze the moderating role of sales in this relationship. A quantitative approach with a causal associative research design was employed, as this study investigates measurable relationships among variables based on company financial report data. The production cost variable was measured using the Cost of Goods Sold (COGS) ratio, profit was measured using the Net Profit Margin (NPM), and sales were used as the moderating variable. The research sample consists of 20 companies in the consumer goods sector, specifically the food and beverage subsector, listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The analytical methods applied were simple linear regression and moderation regression analysis. The results indicate that production costs have a negative and significant effect on profit, suggesting that an increase in the COGS ratio tends to reduce the Net Profit Margin. Furthermore, the moderation test results show that sales do not moderate the effect of production costs on profit. These findings imply that the efficiency of production costs is the key factor determining a company’s profitability, regardless of its sales level. Therefore, management needs to be more careful in controlling production costs by reducing raw material usage and improving labor performance. Through these efforts, companies can maintain their profitability even when production costs increase.